2017
DOI: 10.1186/s13287-017-0705-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and prolonged expansion of oral mesenchymal stem cells under clinical-grade, GMP-compliant conditions differentially affects “stemness” properties

Abstract: BackgroundDevelopment of clinical-grade cell preparations is central to meeting the regulatory requirements for cellular therapies under good manufacturing practice-compliant (cGMP) conditions. Since addition of animal serum in culture media may compromise safe and efficient expansion of mesenchymal stem cells (MSCs) for clinical use, this study aimed to investigate the potential of two serum/xeno-free, cGMP culture systems to maintain long-term “stemness” of oral MSCs (dental pulp stem cells (DPSCs) and alveo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 75 publications
5
76
0
Order By: Relevance
“…B. Liu, Chen, et al, 2012;Moya et al, 2018;J. Zhang, Jia, et al, 2013) Xenofree isolation and culturing (Bakopoulou et al, 2017;Gottipamula et al, 2013;Laitinen et al, 2016;Swamynathan et al, 2014) Abbreviation: MSC, mesenchymal stromal/stem cell.…”
Section: Opportunitiesmentioning
confidence: 99%
“…B. Liu, Chen, et al, 2012;Moya et al, 2018;J. Zhang, Jia, et al, 2013) Xenofree isolation and culturing (Bakopoulou et al, 2017;Gottipamula et al, 2013;Laitinen et al, 2016;Swamynathan et al, 2014) Abbreviation: MSC, mesenchymal stromal/stem cell.…”
Section: Opportunitiesmentioning
confidence: 99%
“…Previously, we showed that bone marrow-derived MSCs (BM-MSCs) and adipose tissue-derived MSCs (ASCs) cultured in a serum-free medium (MesenCult-XF) proliferated faster compared with FBS containing medium but had significantly reduced expression of the MSC marker, CD105 (Brohlin et al 2017). However, to be able to use DPSCs clinically, the cells should be preferably cultivated in a defined medium produced under conditions of current good manufacturing practice (cGMP) (Bakopoulou et al 2017). Previous studies have also shown that human serum was a suitable alternative to FBS for expansion of DPSCs while keeping their angiogenic potential and regenerative capacity (Khanna-Jian et al 2012;Piva et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we found that the ratio of clonogenic cells expressing both STRO-1 and CD146 decreased at > 40 PDL (Table 1; Additional file 2: Table S2). These reductions in the expression ratio of STRO-1 and CD146 were due to the increased number of passages during longterm culture [36,37]. Somoza et al analysed 38 human bone marrow-derived cell clones and found that 10 (26%) were both osteogenic and adipogenic, two (5%) were osteogenic only, 21 (55%) were adipogenic only, and five (13%) did not demonstrate either differentiation potential [15]; notably, these results in bone marrow-derived cell clones were similar to our results in dental pulp-derived cell clones ( Table 2 at 24.1 PDL).…”
Section: Discussionmentioning
confidence: 99%